The Role Of BMPs in the Regulation of Osteoclasts Resorption and Bone Remodeling: From Experimental Models to Clinical Applications - Bordukalo-Nikšić, Tatjana; Kufner, Vera; Vukičević, Slobodan (Frontiers in Immunology, 2022)
In response to mechanical forces and the aging process, bone in the adult skeleton is continuously remodeled by a process in which old and damaged bone is removed by bone-resorbing osteoclasts and subsequently is replaced by new bone by bone-forming cells, osteoblasts. During this essential process of bone remodeling, osteoclastic resorption is tightly coupled to osteoblastic bone formation. Bone-resorbing cells, multinuclear giant osteoclasts, derive from the monocyte/macrophage hematopoietic lineage and their differentiation is driven by distinct signaling molecules and transcription factors. Critical factors for this process are Macrophage Colony Stimulating Factor (M-CSF) and Receptor Activator Nuclear Factor-κB Ligand (RANKL). Besides their resorption activity, osteoclasts secrete coupling factors which promote recruitment of osteoblast precursors to the bone surface, regulating thus the whole process of bone remodeling. Bone morphogenetic proteins (BMPs), a family of multi-functional growth factors involved in numerous molecular and signaling pathways, have significant role in osteoblast-osteoclast communication and significantly impact bone remodeling. It is well known that BMPs help to maintain healthy bone by stimulating osteoblast mineralization, differentiation and survival. Recently, increasing evidence indicates that BMPs not only help in the anabolic part of bone remodeling process but also significantly influence bone catabolism. The deletion of the BMP receptor type 1A (BMPRIA) in osteoclasts increased osteoblastic bone formation, suggesting that BMPR1A signaling in osteoclasts regulates coupling to osteoblasts by reducing bone-formation activity during bone remodeling. The dual effect of BMPs on bone mineralization and resorption highlights the essential role of BMP signaling in bone homeostasis and they also appear to be involved in pathological processes in inflammatory disorders affecting bones and joints. Certain BMPs (BMP2 and -7) were approved for clinical use; however, increased bone resorption rather than formation were observed in clinical applications, suggesting the role BMPs have in osteoclast activation and subsequent osteolysis. Here, we summarize the current knowledge of BMP signaling in osteoclasts, its role in osteoclast resorption, bone remodeling, and osteoblast–osteoclast coupling. Furthermore, discussion of clinical application of recombinant BMP therapy is based on recent preclinical and clinical studies.